Spray-Pyrolysis Synthesised TiO2 Thin Films for Photocatalytic Air Treatment from Volatile Organic Compounds - Jekaterina Sydorenko; Malle Krunks; Arvo Mere; Marina Krichevskaya; Ilona Oja Acik (Proceedings)
A wide range of mixtures of volatile organic compounds (VOCs), which are present in indoor air in low concentrations, can strongly affect human health [...]